ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL UNTUK SISWA SD NEGERI 13 PAJO KABUPATEN DOMPU - Amal Fauqi; Ilham; Vira Oktaviana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This research aims to analyze the need for developing digital learning media for students at SD Negeri 13 Pajo, Dompu Regency. The needs analysis method is carried out through a questionnaire distributed using Google Form so that respondents can fill out the questionnaire online. The respondents were school principals, teachers and students, as well as direct observations of learning conditions at the school. The analysis results show that it is still in the Medium Category average. That there is a significant need for the development of digital learning media that is appropriate to the curriculum and student needs. It is hoped that these findings can become the basis for developing digital learning media that are more effective and support the learning process at SD Negeri 13 Pajo.